Nurel Beautistic (Chocolate Cupcake) / Noranisya Nasaruddin - Nasaruddin, Noranisya (2021)
Nowadays, we know that business is one of the major sources of income for human since the early ages of civilization. Even the Prophet Muhammad once said, “9/10 of income come from businesses”. Therefore, business has a big potential to increase one social standard and living. For my business, that I prepared for this selling project is about chocolate cupcake beauty blender by Nurel Beaustistic Hq. I choose this chocolate cupcake beauty blender by Nurel Beautistic Hq for my business project because I am one of the users. So, this is easier for me to promote because I can prove to other customers with my own. My achievement for this project is RM232 start from 1 May 20121 to 1 June 2021. With this report I will show all activities throughout the sales of this business that I run. In terms of project description before activity, project outcome after activity and experience in sell this chocolate cupcake beauty blender to achieve my sales targets. I decided to sell this product because this is one of the makeup tools that every people love. Not just women but also men. This product also has a higher request in makeup market now.